Keragaan Karakter Morfologi Bawang Merah (Allium ascalonicum L.) Varietas Katumi dan Violetta 3 Agrihorti di Lembang - Mega Nikirahayu; Muhammad Syafi’i; Rika Yayu Agustini; Prasodjo Soedomo (Jurnal Agrotek Indonesia (Indonesian Journal of Agrotech), 2021)
Shallot are one of the popular horticultural commodities that have high economic value in Indonesia. The purpose of this research is to know which variety of shallot that yield the best morphological characters performance in Lembang. This research was conducted at Vegetable Crops Research Institute Lembang, from September to December 2020. The research method used an experimental method single-factor experiment Randomized Complete Block Design (RCBD) consisting of 2 treatments that were repeated 16 times so there are 32 experimental units in total, to find out the best treatment was conducted with Fisher’s Least Significant Difference Test (Fisher’s LSD). The result of research showed that shallot varieties have a significant effect on number of leaves, leaves color, tubers color, tubers shape, dry weight of plants per plot and dry weight of tubers per plot parameter. Treatment of Katumi shallot variety gave the highest yield on parameter tuber diameter (1,88 cm), tuber length (2,42 cm), wet weight of sample plants (63,69 gram), wet weight of plants per plot (704,03 gram), dry weight of sample plants (43,87 gram), dry weight of plants per plot (458,60 gram), dry weight of tuber per sample (40,64 gram) and dry weight of tuber per plot (422,48 gram) meanwhile Violetta 3 Agrihorti shallot variety gave the highest yield on parameter plant height (48,22 cm), number of leaves (42,93 blade), number of tillers (11,40 tillers) and number of tubers (12,60 tubers).